Repeated Doses of Ketamine Affect the Infant Rat Urogenital System - Kasıkara H; Sungu N; Arslan M; Kucuk A; Ozturk L; Afandiyeva N; Kavutcu M (Dove Medical Press, 2021)
Hulya Kasıkara,1 Nuran Sungu,2 Mustafa Arslan,3 Aysegul Kucuk,4 Levent Ozturk,5 Nigar Afandiyeva,6 Mustafa Kavutcu6 1Department of Anaesthesiology and Reanimation, Ankara City Hospital, Ankara, Turkey; 2Medical Faculty, Department of Pathology, Yıldırım Bayazit University, Ankara, Turkey; 3Medical Faculty, Department of Anaesthesiology and Reanimation, Gazi University, Ankara, Turkey; 4Medical Faculty, Department of Physiology, Kutahya Health Sciences University, Kutahya, Turkey; 5Medical Faculty, Department of Anaesthesiology and Reanimation, Yıldırım Bayazit University, Ankara, Turkey; 6Medical Faculty, Department of Biochemistry, Gazi University, Ankara, TurkeyCorrespondence: Mustafa ArslanMedical Faculty, Department of Anesthesiology and Reanimation, Gazi University, Ankara, 06510, TurkeyTel +90 312 202 6739Email mustarslan@gmail.comAim: Long-term ketamine use is known to create an interstitial cystitis-like problem in the bladder. It is known that long-term intermittent ketamine is applied to the children receiving radiotherapy for sedation. This study was planned to investigate whether this effect seen in the bladder causes similar changes in the kidneys, testicles, epididymis and ductus deferens.Materials and Methods: A total of 12 male Wistar Albino rats for 3 weeks were used in the study. Rats were divided equally into 2 groups as, ketamine and saline. 50 mg/kg ketamine was administered intraperitoneally during 21 days to ketamine (K) groups. 1mL/kg saline was administered intraperitoneally during 21 days to saline (S) groups. At the end of 21 days kidney and testicular tissues were taken for biochemical and histopathological evaluations.Results: Histological assessment of kidney tissue showed that tubule epithelial congestion increased significantly in the ketamine group. Epididymis congestion and distortion in the epididymal gland were found to be different in the ketamine group when testicular tissue was examined. Thiobarbituric acid reactive substances (TBARS) level in testicular and kidney tissue was found to be significantly higher in the ketamine group according to the saline group. Catalase (CAT) enzyme activity was significantly lower in the ketamine group compared to the saline group in both tissues. Paraoxonase-1 (PON-1) enzyme activity was significantly higher in the ketamine group compared to the saline group.Conclusion: We think that the results we have achieved in this study will provide guidance on ketamine, which is repeated in daily anesthesia applications, especially in radiation oncology. But these findings should be supported by clinical and experimental studies that will be conducted in a more detailed and broad series.Keywords: ketamine, infant rat, testicular tissue, kidney, epididymis